Sistem Diagnosa Gejala Penyakit Kesehatan Mental Pada Remaja Menggunakan Metode Naïve Bayes - Putri Hana Salsabila; Samsoni (CV. Multi Kreasi Media, 2023)
With the existence of an information technology application program this can help and play a very important role in human life, one of these applications is an application of artificial intelligence carried out by experts, this application is used to solve a problem that is usually only done by an expert in the field of direct knowledge . This application is a website-based application that can help diagnose a mental health disease that often occurs in adolescents. The purpose of this application is to diagnose a mental health disease in adolescents and help adolescents to find out whether they are experiencing symptoms of mental health disease or not. This data collection method is carried out in several ways, namely by the method of Observation, Interview and Literature Study, the results of the data collection are then collected and calculated using the Naïve Bayes calculation method, from these data will then be inputted into a website-based application that previously created, this application is made using the PHP programming language and uses the MySQL database. The results and benefits expected in making this thesis are to increase knowledge about mental health so that everyone can be more aware in responding to this, besides that this application is also expected to be able to help a teenager who wants to know about his mental health condition, and is expected to help in alleviating the work of an expert in diagnosing the disease so that the settlement process will be faster and more accurate.